Extensive mitochondrial heteroplasmy in the neotropical ants of the Ectatomma ruidum complex (Formicidae: Ectatomminae). (17th November 2018) - Meza-Lázaro, Rubi N.; Poteaux, Chantal; Bayona-Vásquez, Natalia J.; Branstetter, Michael G.; Zaldívar-Riverón, Alejandro
Abstract: We assembled mitogenomes from 21 ant workers assigned to four morphospecies ( E. ruidum spp. 1-4) and putative hybrids of the Ectatomma ruidum complex ( E. ruidum spp. 2x3), and to E. tuberculatum using NGS data. Mitogenomes from specimens of E. ruidum spp. 3, 4 and 2 × 3 had a high proportion of polymorphic sites. We investigated whether polymorphisms in mitogenomes are due to nuclear mt paralogues ( numts ) or due to the presence of more than one mitogenome within an individual (heteroplasmy). We did not find loss of function signals in polymorphic protein-coding genes, and observed strong evidence for purifying selection in two haplotype-phased genes, which indicate the presence of two functional mitochondrial genomes coexisting within individuals instead of numts . Heteroplasmy due to hybrid paternal leakage is not supported by phylogenetic analyses. Our results reveal the presence of a fast-evolving secondary mitochondrial lineage of uncertain origin in the E. ruidum complex.